Risk assessment and aspirin use in Asian and Western populations - Runlin Gao; Xiaoying Li (Vascular Health and Risk Management, 2010)
Runlin Gao1, Xiaoying Li21Department of Cardiology, Cardiovascular Institute and Fuwai Hospital, Chinese Academy of Medical Sciences, Beijing; 2Department of Geriatric Cardiology, Chinese PLA General Hospital, Beijing, ChinaObjective: The aim of this review was to examine aspirin utilization, cardiovascular risk estimation, and clinical evidence for aspirin prophylaxis in Asian versus Western countries.Methods: A literature search was performed using PubMed and the key terms "aspirin" and "Asia" or "Western".Results: Despite the growing burden of cardiovascular disease (CVD), aspirin is underutilized in high-risk patients in both Asian and Western countries. A number of risk estimation scores are available; however, validation is needed in countries such as Japan, India, and in South Asia. Underutilization of aspirin in Asia may be linked to an overestimation of bleeding risks. It is possible that a higher prevalence of Helicobacter pylori infection and genetic differences may make Asians more susceptible to gastrointestinal bleeding. Very low aspirin doses and even the wider use of gastroprotective agents may be the optimal approach to high-risk patients in Asia.Conclusions: Based on the current evidence, aspirin should be used for CVD prevention when the risk:benefit ratio is favorable. A number of trials are underway, including the Diabetic Atherosclerosis Prevention by Cilostazol and Japanese Primary Prevention Project, which will provide key data on the benefits of aspirin in Asian patients at risk of CVD, and may improve aspirin utilization and risk estimation.Keywords: aspirin, cardiovascular risk estimation, Asia, Western